Structural, Physical, Theoretical and Spectroscopic Investigations of Mixed‐Valent Eu2Ni8Si3 and Its Structural Anti‐Type Sr2Pt3Al8. Issue 37 (26th August 2021) - Stegemann, Frank; Block, Theresa; Klenner, Steffen; Zhang, Yuemei; Fokwa, Boniface P. T.; Doerenkamp, Carsten; Eckert, Hellmut; Janka, Oliver
Abstract: Eu2 Ni8 Si3 and its anti ‐type representative Sr2 Pt3 Al8 were synthesized from the elements. They crystallize in the tetragonal crystal system with space group P 42 / nmc and with lattice parameters of a =997.9(1) and c =747.6(1) pm (Eu2 Ni8 Si3 ) as well as a =1082.9(2) and c =823.3(2) pm (Sr2 Pt3 Al8 ). Both compounds were investigated via single crystal X‐ray diffraction, indicating slight Si/Ni mixing for the silicide. Sr2 Pt3 Al8 exhibits a temperature independent magnetic susceptibility, suggesting superimposed dia‐ and Pauli ‐paramagnetic contributions. The independent Al and Pt sites of the platinide were further characterized by 27 Al and 195 Pt solid‐state NMR spectroscopy, which were assigned with the help of electronic structure calculations. ICOHP calculations and Bader charges were used to analyze the bonding situation. Eu2 Ni8 Si3 in contrast is paramagnetic with a ferromagnetic transition at T C =46.9(2) K and exhibits an effective magnetic moment of μ eff =6.61(1) μB per Eu atom. The latter is in line with an intermediate valence that was further proven by 151 Eu Mößbauer spectroscopic investigations. At 300 K, the refined Eu 2+ /Eu 3+ ratios are 60 %/40 %, at 78 K 62 % and 38 % (Eu 2+ /Eu 3+ ) are observed, being in line with the ratio deduced from the magnetic susceptibility. Finally, at 6 K a ratio of 68 % Eu 2+ and 32 % Eu 3+ was observed. Below the Curie temperature, the Eu 2+ signal shows a full magnetic hyperfine splitting, with an internal magnetic field value of B 0 =28.4 T. Abstract : The intermetallic compounds Eu2 Ni8 Si3 and Sr2 Pt3 Al8 were synthesized and characterized via single crystal X‐ray diffraction. Their magnetic properties were determined showing with an intermediate Eu valence state which was further investigated by 151 Eu Mößbauer spectroscopic measurements. Furthermore, NMR investigations in combination with quantum chemical calculations were employed.